Unsteady convection flow of a magnetomicropolar fluid past a vertical porous plate - Jain, N.C.; Gupta, Pragati; Sharma, B. (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with an unsteady two dimensional laminar slip flow of a viscous incompressible magnetomicropolar fluid past a semi infinite porous plate embedded in a porous medium. The flow is under the influence of a transverse magnetic field and heat source/sink. The free stream velocity follows an exponentially increasing or decreasing small perturbation law. The porous surface absorbs the fluid with time varying suction velocity. Expressions are obtained for velocity and temperature fields, mean angular velocity, skin friction and the Nusselt number.
Keywords: heat source/sink; magnetic field; porous medium; slip velocity; unsteady; vertical plate